Healthy eating determinants and dietary patterns in European adolescents: the HELENA study. Issue 1 (1st January 2019) - González-Gil, Esther M.; Martínez-Olivan, Beatriz; Widhalm, Kurt; Lambrinou, Christina P; Henauw de, Stefan; Gottrand, Frederic; Kafatos, Antonios; Beghin, Laurent; Molnar, Denes; Kersting, Mathilde; Leclercq, Catherine; Sjöström, Michael; et al.
ABSTRACT: Background/Objectives : To assess dietary patterns (DPs) in European adolescents and to examine their relationship with healthy eating determinants. Subject/Methods : A total of 2205 European adolescents, aged 12.5–17.5 years, were measured. A self-reported questionnaire was completed and dietary intake was measured by 24 h-dietary recalls. Principal component analysis was performed to obtain DPs. Analyses of covariance was used to examine the associations. Results : Four DPs for boys and six DPs for girls were obtained. Boys with healthier DPs, i.e. "plant-based" and "breakfast", had lower availability of soft drinks at home, higher perception of benefits of healthy eating and higher awareness of what is a healthy diet. Girls with healthy DPs ("Mediterranean", "plant-based", "healthy breakfast") had significantly higher fruits and lower soft drinks availability, higher perception of benefits, lower perception of barriers for a healthy eating and higher awareness of what is a healthy diet. Conclusion : Healthier DPs were related with availability of healthy foods, perceived benefits and awareness of the diet. In contrast, those with other patterns had lower availability of fruits and higher availability of soft drinks at home, no perception of the benefits of healthy eating and they were aware that their diet was not healthy.